2014
DOI: 10.1177/1470320313516174
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism inAGTandAGTR1gene is associated with lead-related high blood pressure

Abstract: We investigated the association of polymorphisms in two renin-angiotensin system-related genes, expressed as angiotensinogen (AGT) and angiotensin II type 1 receptor (AGTR1), with blood lead levels and lead-related blood pressure in lead-exposed male workers in Korea. A cross-sectional study involving 808 lead-exposed male workers in Korea was conducted using a restriction fragment length polymorphism-based strategy to differentiate the various genotypes of polymorphisms in the AGT and AGTR1 genes. The associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 50 publications
0
18
0
4
Order By: Relevance
“…A1166C is located at the 5′ end of the 3′ untranslated region of the gene [72]. This location is a non-coding region of AT1R, and it is linked to disequilibrium with a nearby mutation that may affect AT1R messenger ribonucleic acid (mRNA) stability [32]. In essential hypertension, the C allele of A1166C was revealed to have a pivotal role for influencing AT1R activities through affecting mRNA stability and transcription or alternatively be linked to other SNPs [65].…”
Section: Discussionmentioning
confidence: 99%
“…A1166C is located at the 5′ end of the 3′ untranslated region of the gene [72]. This location is a non-coding region of AT1R, and it is linked to disequilibrium with a nearby mutation that may affect AT1R messenger ribonucleic acid (mRNA) stability [32]. In essential hypertension, the C allele of A1166C was revealed to have a pivotal role for influencing AT1R activities through affecting mRNA stability and transcription or alternatively be linked to other SNPs [65].…”
Section: Discussionmentioning
confidence: 99%
“…В связи с этим, обращение многих исследо-вателей к изучению генетических основ гипертрофии кардиомиоцитов вполне обоснованно и перспек-тивно. Получены многочисленные, крайне важные результаты роли полигенных нарушений в течении и исходе ЭАГ и ассоциаций полиморфизмов генов РААС, симпатоадреналовой системы, генов, ответ-ственных на синтез сократительных белков кардио-миоцитов и др., с фактом ГЛЖ [8,9,11,12,14]. Отли-чительными особенностями результатов этих популя-ционно-генетических исследований являются уникальность распределения частот полиморфизмов генов-кандидатов в зависимости от этнической, ген-дерной принадлежности, а также географического района проживания исследуемых пациентов.…”
Section: Discussionunclassified
“…Генотипирование полимор-физмов Тhr174Мet и Мet235Тhr гена AGT, полимор-физм A1166C гена AGTR1 проводили с использова-нием наборов для генотипирования "SNP-ЭКС-ПРЕСС-РВ-Кардиогенетика". Согласно инструкции к этому набору, с образцом выделенной ДНК прово-дили одновременно две реакции амплификации -но полиморфизмы AGTR1 не имели статистически доказанной связи с ГЛЖ [12]. Исследование Т174М полиморфизма гена AGT показало более высокую распространенность М-аллеля в гомозиготном состо-янии у больных АГ с ГЛЖ [13].…”
Section: Analysis Of Polymorphisms Of Renin-angiotensin-aldosterone Sunclassified
“…A number of genes and gene encoding proteins have been identified to play important roles in lead toxicokinetics and/or toxicodynamics: δ-aminolevulinic acid dehydratase (ALAD), an enzyme on the heme-biosynthetic pathway that binds over 80% of lead in erythrocytes [9]; hemochromatosis (HFE), a membrane protein that regulates uptake of cellular iron and other divalent metals including lead [10]; heme oxygenase-1 (HMOX1), a heme-degrading enzyme that plays an important role in the inflammation and oxidative stress induced by lead [11][12][13][14]; vitamin D receptor (VDR) that plays a role in calcium homeostasis that influences the absorption and retention of lead into blood and bone [15]; apolipoprotein E (APOE) that affects lipid metabolism, down-regulates blood lead concentrations, and possesses antioxidative property [16][17][18]; glutathione S-transferases (GSTs), a family of phase-II detoxification isozymes involved in catalyzing the conjugation of lead and glutathione to form a thermodynamically stable complex, which decreases lead bioavailability and protects against lead toxicity through reduced oxidative stress [19][20][21][22]; and the renin-angiotensin system involved in the development of hypertension where lead exposure may enhance blood angiotensin I levels by increasing plasma renin activity, which in turn contribute to production and activation of substrate-induced angiotensin converting enzyme [23,24]. Epidemiologic studies have identified that these genes may modify the association between lead exposure and cardiovascular and other health outcomes [13,18,[25][26][27]. However, these previous studies focused on one or a few of the lead-related genetic polymorphisms.…”
Section: Introductionmentioning
confidence: 99%